Links between parental life histories of wild salmon and the telomere lengths of their offspring - Darryl McLennan; John D. Armstrong; David C. Stewart; Simon McKelvey; Winnie Boner; Pat Monaghan; Neil B. Metcalfe (Molecular Ecology, 2018)
The importance of parental contributions to offspring development and subsequent performance is self‐evident at a genomic level; however, parents can also affect offspring fitness by indirect genetic and environmental routes. The life history strategy that an individual adopts will be influenced by both genes and environment; and this may have important consequences for offspring. Recent research has linked telomere dynamics (i.e., telomere length and loss) in early life to future viability and longevity. Moreover, a number of studies have reported a heritable component to telomere length across a range of vertebrates, although the effects of other parental contribution pathways have been far less studied. Using wild Atlantic salmon with different parental life histories in an experimental split‐brood in vitro fertilization mating design and rearing the resulting families under standardized conditions, we show that there can be significant links between parental life history and offspring telomere length (studied at the embryo and fry stage). Maternal life history traits, in particular egg size, were most strongly related to offspring telomere length at the embryonic stage, but then became weaker through development. In contrast, paternal life history traits, such as the father's growth rate in early life, had a greater association in the later stages of offspring development. However, offspring telomere length was not significantly related to either maternal or paternal age at reproduction, nor to paternal sperm telomere length. This study demonstrates both the complexity and the importance of parental factors that can influence telomere length in early life.